Role of R&D alliances in Pharma-Biotech Industry Case study of Indian Industry - Hanzra, Inderpreet Kaur (2007)
In today's intensely competitive business milieu, pharmaceutical companies are increasing their product pipelines by both developing drugs on their own and also by R&D alliances. This study attempts to understand the importance and need of R&D alliances in pharmaceutical and biotech industry. Declining product pipelines and astringent patent law across the world are bothering the companies and they are relying on strategic alliances to speed up the process of innovation. Strategic alliances are long-term agreements between legally distinct organizations that provide mutually beneficial activity by sharing the risks and benefit. Indian Pharmaceutical industry is growing at a fast pace and competing with global pharmaceutical companies. The most common strategic concern that Trade Related Aspects of Intellectual Property Rights (TRIPs) has raised for Indian firms is the perceived need for R&D and technological strength. For companies that have given little attention to R&D and innovation in the past, this transition is not very easy. Indian firms have responded well to these changes and are undergoing strategic alliances to meet the business needs and prove winners in long run. Biotech industry in India is also growing at alarming rate, and is helping pharmaceutical companies develop their product pipeline by providing advanced technologies. Employing firm-level case studies, this research examines the strategic alliance approach adopted by leading Indian industries (Ranbaxy and Biocon) to enhance their drug pipelines. Using case study findings, this report shows how pharma and biotech firms are relying on alliances for innovation. Results confirm that alliances enhance the innovation and help companies to have strong hold in market by keeping their product pipeline flowing.